Best Answer

x(x-1)(x-1)FOIL

SIMPLIFY

TIMES EVERYTHING IN THE BRACKETS BY X

i will let you work it out

Study guides

☆☆

Q: How do you expand fully and simplify x open bracket x-1 close bracket squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3(7a - 5b) + 2(4a - 3b) Multiply the contents of each bracket by the number outside it: 21a - 15b + 8a - 6b Bring like terms together: 21a + 8a - 15b - 6b Combine like terms: 29a - 21b This cannot be simplified further.

7C MINUS bracket open c plus 2 bracket close equals 7c minus c minus 2 equals 6c minus 2

-(3x-4) = -3x + 4

Trial and error. You know that the answer will be between 2 and 3, closer to 3. 2.8 squared = 7.84 2.82 squared = 7.95 2.828 squared = 7.99 2.8284 squared = 7.999 which is close enough for me.

Roughly close to something near 289.

Related questions

7(a + 3) = 7*a + 7*3 = 7a + 21

sure... I bet lots of people can simplify this... How 'bout 5x sq -15

x cubed y cubed z squared

3(7a - 5b) + 2(4a - 3b) Multiply the contents of each bracket by the number outside it: 21a - 15b + 8a - 6b Bring like terms together: 21a + 8a - 15b - 6b Combine like terms: 29a - 21b This cannot be simplified further.

(x2y2)3 + (x3y3)2 = 2x6y6.

(x-2)(x+2)= x2+2x-2x-4= x2-4

(:)+< Open bracket, :, close bracket, plus, < less then

you first solve the inside of the bracket and then do the inside answer with the outside numbers.

7C MINUS bracket open c plus 2 bracket close equals 7c minus c minus 2 equals 6c minus 2

2(2*1) = 2(2) = 4

-(3x-4) = -3x + 4

I think I'm answering my own quezstion here but hey. Am I right in saying that (x+0)(x+1) Factorises to x2+ x? I think I am.

People also asked

Featured Questions